IMPLEMENTASI PERATURAN MENTERI SOSIAL REPUBLIK INDONESIA NOMOR 7 TAHUN 2017 TENTANG STANDAR HABILITASI DAN REHABILITASI SOSIAL PENYANDANG DISABILITAS PADA MASA PANDEMI COVID-19 DI BALAI REHABILITASI SOSIAL PENYANDANG DISABILITAS FISIK (BRSPDF) BUDI PERKAS - Supardi Supardi; Resi Muliana (Fakultas Pertanian, 2022)
Social rehabilitation center for people with physical disabilities (brspdf) budi perkasa palembang during the covid-19 pandemic, problems were found related to the covid-19 pandemic, namely the social rehabilitation service program at the rehabilitation center still relies on service program processes that are not optimal, which are constrained by the covid pandemic. -19. Has a problem formulation how is the implementation of the regulation of the minister of social affairs of the republic of indonesia number 7 of 2017 concerning standards for habilitation and social rehabilitation of persons with disabilities at the budi perkasa social rehabilitation center for physical disabilities palembang during the covid-19 pandemic. The purpose of this study was to analyze the implementation of the regulation of the minister of social affairs of the republic of indonesia number 7 of 2017 concerning standards for social habilitation and rehabilitation of persons with disabilities at the budi perkasa social rehabilitation center for physical disabilities palembang during the covid-19 pandemic. The method used in this research is a qualitative research methodology. The concept used in the research is the implementation and standards of social rehabilitation and rehabilitation. The data sources used are primary and secondary data. Based on the data analysis carried out, it was concluded that communication is still not optimal because during the covid-19 pandemic communication is influenced by cellphones, computers, internet data packages, pulses, and internet networks whose communication process is carried out by working from home or wrok from home. Wfh). Human resources during the covid-19 pandemic still have to be optimized because balai cannot accommodate persons with disabilities who must be rehabilitated in large numbers and for a limited period of time. 19 through the atensi program made adjustments by increasing the number to receive services outside the balai to approximately 2,275 persons with physical disabilities. This greatly affects work patterns and budgeting patterns, which initially became slightly larger, while the correlative hr remained. The inhibiting factor is the existence of the covid-19 pandemic, there are restrictions that cause mobility to be hampered so that the capacity of persons with disabilities at the balai is reduced and there are several employees who are exposed to the covid-19 virus. ABSTRAK Tujuan dari penelitian ini adalah untuk menganalisis pelaksanaan Peraturan Menteri Sosial Republik Indonesia Nomor 7 Tahun 2017 tentang Standar Pembinaan dan Rehabilitasi Sosial Penyandang Disabilitas di Balai Rehabilitasi Sosial Budi Perkasa Untuk Cacat Fisik Palembang. selama pandemi covid-19. Metode yang digunakan dalam penelitian ini adalah metodologi penelitian kualitatif. Konsep yang digunakan dalam penelitian ini adalah pelaksanaan dan standar rehabilitasi dan rehabilitasi sosial. Sumber data yang digunakan adalah data primer dan data sekunder. Berdasarkan analisis data yang dilakukan, disimpulkan bahwa komunikasi masih belum optimal karena pada masa pandemi covid-19 komunikasi dipengaruhi oleh ponsel, komputer, paket data internet, pulsa, dan jaringan internet yang proses komunikasinya dilakukan dengan bekerja dari rumah atau bekerja dari rumah. wfh). Sumber daya manusia di masa pandemi covid-19 masih harus dioptimalkan karena Balai tidak dapat menampung penyandang disabilitas yang harus direhabilitasi dalam jumlah besar dan dalam jangka waktu terbatas. 19 melalui program atensi dilakukan penyesuaian dengan menambah jumlah penerima pelayanan di luar balai menjadi kurang lebih 2.275 penyandang disabilitas fisik. Hal ini sangat mempengaruhi pola kerja dan pola penganggaran yang awalnya menjadi sedikit lebih besar, sedangkan jam korelatif tetap ada. Faktor penghambatnya adalah adanya pandemi covid-19, ada pembatasan yang menyebabkan mobilitas terhambat sehingga daya tampung penyandang disabilitas di balai berkurang dan ada beberapa pegawai yang terpapar virus covid-19